Diabetes Hospitalization at the U.S.-Mexico Border - Juan R. Albertorio-Diaz, MA; Francis C. Notzon, PhD; Alfonso Rodriguez-Lainz, DVM, MPH (Centers for Disease Control and Prevention, 2007)
IntroductionThe diabetes hospitalization rate for the region along the U.S. side of the U.S.-Mexico border is unknown, a situation that could limit the success of the Healthy Border 2010 program. To remedy this problem, we analyzed and compared hospital discharge data for Arizona, California, and Texas for the year 2000 and calculated the diabetes hospitalization rates.MethodsWe obtained hospital-discharge public-use data files from the health departments of three U.S. border states and looked for cases of diabetes. Only when diabetes was listed as the first diagnosis on the discharge record was it considered a case of diabetes for our study. Patients with cases of diabetes were classified as border county (BC) or nonborder county (NBC) residents. Comparisons between age-adjusted diabetes discharge rates were made using the z test.ResultsOverall, 1.2% (86,198) of the discharge records had diabetes listed as the primary diagnosis. BC residents had a significantly higher age-adjusted diabetes discharge rate than NBC residents. BC males had higher diabetes discharge rates than BC females or NBC males. In both the BCs and the NBCs, Hispanics had higher age-adjusted diabetes discharge rates than non-Hispanics.ConclusionThe results of this study provide a benchmark against which the effectiveness of the Healthy Border 2010 program can be measured.